Tradução e adaptação cultural do instrumento: “The SACS TM Instrument” - Silveira, Néria Invernizzi da (2018)
Introduction: The skin around the ostomy should be evaluated constantly because of the risk of having its integrity impaired and there is no instrument validated in Brazil for assessment and classification of the lesions and topographic location. Objective: To carry out the cultural adaptation of "The SACS™ Instrument" for use in Brazil and assess content validity, inter-observer reliability and evaluate the educational dimension to the understanding of this instrument. Method: This is a methodological study with a quantitative and qualitative approach. The cultural adaptation was elaborated by four translators in the translation and back-translation phases and its summaries were compiled by the author. The content validity index (CVI) was analyzed by seven judges for semantic, idiomatic, cultural and conceptual equivalences. The formula for calculating the CVI was the addition of the answers, divided by the total number of answers. Inter-observer reliability came from the investigation of 41 photographs, carried out by two nurses who specialize in stomatherapy and the values were presented in percentage and with the weighted kappa coefficient (K). To achieve instrument validity a focus group strategy was used, with eight students from year four of the undergraduate nursing program. Result: The result obtained for SACS™ Instrument was IVC=1. Reliability for the evaluation and classification of the lesions presented agreement of 41.18% and K = 0.2444, and for topographic location resulted in 46.67% and K = 0.3151. Another measure of interobserver agreement was the level of statistical significance that presented p <0.001 and was found to be extremely significant. Discussion: The process of translation and cultural adaptation was developed with the scientific rigor of the research objective. IVC = 1 was the same as that in a study in Turkey. In Italy and the USA, IVC = 0.91 and IVC = 0.94, respectively, demonstrated the viability in clinical practice, but with specific training. Conclusion: The SACSTM instrument was translated and adapted to Brazilian Portuguese culture and meant to be an internationally standardized tool and useful in clinical practice for the evaluation, classification, topographic location of peristomial lesions, certifying reliable results and that met the objectives of this study